SIRI’ DAN PACCE DALAM EPISODE PERJALANAN SAWERIGADING KE TANAH CINA - Aminuddin Ram (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
This paper deals with the so called siri’ and pacce which are the most important values in Buginese-Makassarese culture. The paper attempts to observe these two values as reflected in the episode of Sompe’na Sawerigading Lao ri Tanah Cina (Sawerigading’s Journey to Tanah Cina) which is one of the episodes of Lagaligo, the longest world literary work recognized by Unesco (United Nations, Educational, Social, and Cultural Organization) as a Memory of the World (MOW) in 2011. Siri’ and pacce, which are the core values of Buginese-Makassarese culture, function as a source of moral reference that strongly influences the way of thinking and behavior of Buginese-Makassarese people. The paper reveals that several characters in the story of Sompe’na Sawerigading Lao ri Tana Cina try to do their best to observe the two values in facing conflicts and challenges of life, but some of them fail. This is due to the fact that the implementation of siri’ and pacce may vary in accordance with one’s status, emotional and intellectual maturity as well as motivation. It is recommended that in order to reduce the destructive impacts of globalization and to minimize the deterioration of national identity and character there should be a holistic strategic policy and efforts taken both by the state and private institutions to seriously and continuously facilitate the transformation of noble values.